Contextual Analysis of Digital Halal Tourism Development Feasibility in Talango Village, Sumenep: An Exploratory Qualitative Study - Zainorrahman; Robby Reza Zulfikri (FEBI IAIN Langsa, 2026)
Although digital halal tourism is growing rapidly, most studies still focus on urban destinations and quantitative approaches, thus leaving a gap in the in-depth understanding of how rural Muslim communities negotiate the integration of digital technology with Islamic values and local wisdom. This study addresses this gap through an intrinsic qualitative case study in Talango Village, Sumenep, Madura. Using an intrinsic qualitative case study approach, data were collected through semi-structured interviews with 15 purposively selected informants, participant observation, and documentary analysis during the period from February to May 2025. Thematic analysis revealed three main themes: (1) the community’s high enthusiasm for halal tourism that is not matched by the readiness of infrastructure and digital services; (2) the low level of literacy and access to sharia financial technology; and (3) socio-cultural resistance to digitalization, which is feared to erode the sacredness of Islamic values. This study contributes theoretically to the halal tourism literature by developing a contextual-religious perspective that highlights the tension between digital innovation and the preservation of spiritual identity in rural Muslim communities—a dimension that is still rarely discussed in existing studies, which tend to be universalistic and market-oriented. Thus, this research enriches the theory of innovation diffusion and Islamic value-based tourism development in rural contexts.